2022
DOI: 10.1161/hypertensionaha.121.18298
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in XO (Xanthine Oxidase) and Mitochondrial DNA Damage-Associated Molecular Patterns in Resistant Hypertension

Abstract: Background: We previously reported increased plasma XO (xanthine oxidase) activity in patients with resistant hypertension. Increased XO can cause mitochondrial DNA damage and promote release of fragments called mitochondrial DNA damage-associated molecular patterns (mtDNA DAMPs). Here, we report racial differences in XO activity and mtDNA DAMPs in Black and White adults with resistant hypertension. Methods: This retrospective study includes 91 resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous studies have suggested that ccf-mtDNA may be associated with spontaneous hypertension in rats 14 , in resistant hypertension in African American men and women 13 as well as in the hypertension-related condition, pre-eclampsia. 55 There is also some evidence that ccf-mtDNA is present in the urine hypertensive African American patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that ccf-mtDNA may be associated with spontaneous hypertension in rats 14 , in resistant hypertension in African American men and women 13 as well as in the hypertension-related condition, pre-eclampsia. 55 There is also some evidence that ccf-mtDNA is present in the urine hypertensive African American patients.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Few studies have explored the role of ccf-mtDNA in the context of hypertension. 7 , 12 , 13 , 14 mtDNA levels of the mitochondrially encoded NADH dehydrogenase 1 and 6 ( MT-ND1 , MT-ND6 ) are significantly higher in the plasma of patients with resistant hypertension (n = 91) compared with controls (n = 37), with mtDNA levels significantly higher in Black patients (n = 40) compared with White patients (n = 51) with resistant hypertension. 13 McCarthy et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the known role of inflammation and oxidative stress in persons with HF, 5,42 more work is needed to better understand the role of cellular aging in the context of the HF inflammatory milieu. Telomerase dysfunction and shorter leukocyte telomere length are associated with increased cardiovascular risk and mortality 43 and should be considered as part of the pathophysiological changes that lead to cardiovascular disease risk and development.…”
Section: Discussionmentioning
confidence: 99%
“…One unit of activity (U) was defined as 1 μmole/min urate formed at 37 °C and pH 7.4. Results were expressed as a concentration relative to total sample protein content [ 35 ]. Inter- and intra-assay variability were less than 10 %.…”
Section: Animal Modelmentioning
confidence: 99%